Early Health Detection among Housewives to Enhance Family Health and Well-Being - Alvian Pristy Windiramadhan; Rd. Gita Mujahidah; Dewi Eka Stia Murni (Lembaga Penerbitan Fakultas Kesehatan, Universitas Kristen Indonesia Maluku, 2025)
Early detection of non-communicable diseases (NCDs) is a strategic effort to raise public health awareness, especially among housewives who play a central role in maintaining family welfare. This community service activity aims to conduct basic health screenings, including blood pressure measurements, blood glucose levels, and Body Mass Index (BMI) assessments, among housewives participating in the Enhancing Women's Roles Towards Healthy and Prosperous Families (P2WKSS) program in Haurgeulis Village, Haurgeulis Subdistrict, Indramayu Regency. The activity was conducted through simple health examinations followed by discussions and education on healthy lifestyles. The results of the examination of 60 participants showed that the majority of respondents were in the pre-hypertension to hypertension category (87%), (25%) were in the pre-diabetes to diabetes category, and (63%) were overweight to obese. These findings indicate a high risk factor for NCDs among housewives in the area. This early detection program not only provides an initial overview of the community's health condition but also serves as a means of education and empowerment for housewives to be more concerned about their own health and that of their families. Thus, this activity supports the achievement of the Sustainable Development Goals (SDGs), particularly the third goal on good health and well-being, and the fifth goal on gender equality through empowerment.